Patch testing for allergic contact dermatitis to cigarettes: Smoked/unsmoked components and formaldehyde factors. (5th September 2013) - Carew, Benjamin; Muir, Jim
Abstract A patient with hand dermatitis reported that switching her smoking hand resulted in reduced symptoms. When allergy to cigarettes is suspected the literature supports standard allergy testing as well as testing the individual components of cigarettes. Initial standard patch testing revealed an allergy to formaldehyde and the formaldehyde releasing agent, quaternium‐15. The patient did not react to her usual roll‐your‐own cigarette components but reacted to the smoked filter paper of a particular brand of cigarette she frequently borrowed from a friend. Possible explanations include either a variation of ingredients between cigarettes that alters the formaldehyde concentration or another unidentified allergen in the branded cigarette causing allergic contact dermatitis.